Who Rules the World : Divine Providence and the Existence of Evil - Schwarz, Hans, 1939- (Book collections on Project MUSE., 2021)
How is it possible to reconcile the manifest evil and pain in the world with the biblical promise of hope and redemption? To this question, Schwarz brings both pastoral sensitivity and scholarly acumen. Informed by decades in the classroom, Schwarz offers a sweeping survey across the broad span of Christian history. The book aims to help readers understand the broad sweep of human thought and make informed assessments of the issue for themselves.